Giant Coronary Artery Aneurysms in Kawasaki Disease Detected by Multi Detector Computed Tomographic - Oktavia Lilyasari; Poppy S Roebiono; Radityo Prakoso; Anna Ulfah Rahajoe; Indriwanto Sakidjan; Ganesja M Harimurti (The Indonesian Heart Association, 2013)
Kawasaki disease is an acute, self -limited vasculitis of unknown etiology that occurs predominantly in infants and young children. The major sequele of Kawasaki disease are related to the coronary arterial system. Cardiac imaging is a critical part in evaluation of all patients with suspected Kawasaki disease. Multi Detector CT (MDCT) provides a safe non-invasive approach to accurately delineate coronary artery anatomic structure. We report a case of a 6 years old boy with history of Kawasaki disease. Multi detector CT scan showed giant aneurysm at proximal LAD, proximal RCA and medium aneurysm at proximal LCX. Patient then treated with the anticoagulant therapy.